Effects of Inductive and Deductive Inquiry Teaching Approaches on Technical College Students Achievement in Metalwork - Muhammad Abubakar Uthman; Emmanuel Okafor Ede; Abdullahi Muhammad Hassan (Advanced Journal of STEM Education, 2024)
The impact of inductive and deductive teaching methods on metalwork proficiency was evaluated among technical college students. The purpose of study was designed to determine the effect of inductive and deductive inquiry teaching approaches to enhance students’ cognitive achievement in Metalwork and to students’ psychomotor achievement in Metalwork. The study, involving 115 students, employed a pre-test, post-test, non-equivalent control group design, with 56 students allocated to the Deductive Inquiry group and 59 to the Inductive Inquiry group. Data were collected using the Metalwork Achievement Test (MCAT) and the Metalwork Psychomotor Achievement Test (MPAT). The Pearson Product Moment Correlation produced a correlation coefficient of 0.83 for assessing the MCAT's reliability. The reliability of MPAT was determined using the scorer dependability technique. The inter-rater agreement was 0.82. Despite a non-significant ANCOVA result at the 0.05 level, the students in the experimental groups showed superior mean scores. In metalwork instruction, students who employed the inductive inquiry method earned higher average scores on both the cognitive and psychomotor tests. The mean scores were statistically significant. Given these findings, Metalwork teachers at technical colleges should employ an inquiry-based learning method.